Intestinal Protists in Captive Non-human Primates and Their Handlers in Six European Zoological Gardens. Molecular Evidence of Zoonotic Transmission - Köster, Pamela C.; Martínez-Nevado, Eva; González, Andrea; Abelló-Poveda, María T.; Fernández-Bellon, Hugo; de la Riva-Fraga, Manuel; Marquet, Bertille; Guéry, Jean-Pascal; Knauf-Witzens, Tobias; Weigold, Annika; Dashti, Alejandro; Bailo, Begoña; et al. (Frontiers in Veterinary Science, 2022)
We assessed the occurrence, genetic diversity, and zoonotic potential of four protozoan (Cryptosporidium spp., Entamoeba histolytica, Entamoeba dispar, Giardia duodenalis), one stramenopile (Blastocystis sp.), one microsporidia (Enterocytozoon bieneusi), and two ciliate (Balantioides coli, Troglodytella abrassarti) intestinal parasite or commensal protist species in captive non-human primates (NHP) and their zookeepers from six European zoological gardens in France (n = 1), Germany (n = 1), and Spain (n = 4). Faecal samples from NHP (n = 454) belonging to 63 species within 35 genera and humans (n = 70) were collected at two sampling periods in each participating institution between October 2018-August 2021. Detection and species identification was accomplished by PCR and Sanger sequencing of the ssu rRNA and/or ITS genes. Sub-genotyping analyses using specific markers were conducted on isolates positive for G. duodenalis (gdh, bg, tpi) and Cryptosporidium sp. (gp60). Overall, 41.0% (186/454) and 30.0% (21/70) of the faecal samples of NHP and human origin tested positive for at least one intestinal protist species, respectively. In NHP, Blastocystis sp. was the most prevalent protist species found (20.3%), followed by G. duodenalis (18.1%), E. dispar (7.9%), B. coli and T. abrassarti (1.5% each), and Cryptosporidium spp. and E. bieneusi (0.9% each). Occurrence rates varied largely among NHP host species, sampling periods, and zoological institutions. The predominant protist species found in humans was Blastocystis sp. (25.7%), followed by Cryptosporidium spp. (2.9%), E. dispar (1.4%), and G. duodenalis (1.4%). Sequencing of PCR-positive amplicons in human and/or NHP confirmed the presence of Cryptosporidium in six isolates (C. hominis: 66.7%, C. parvum: 33.3%), G. duodenalis in 18 isolates (assemblage A: 16.7%, assemblage B: 83.3%, Blastocystis in 110 isolates (ST1:38.2%, ST2:11.8%, ST3: 18.2%, ST4: 9.1%, ST5: 17.3%, ST8: 2.7%, ST13: 0.9%), and E. bieneusi in four isolates (CM18: 75.0%, Type IV: 25.0%). Zoonotic transmission events involving Blastocystis ST1‒ST4 were identified in four zoological institutions. Zoonotic transmission of C. hominis was highly suspected, but not fully demonstrated, in one of them. Monitoring of intestinal protist species might be useful for assessing health status of captive NHP and their zookeepers, and to identify transmission pathways of faecal-orally transmitted pathogens.